Prévalence De l’Obésité En Milieu Jeune En Côte d’Ivoire - Kouakou, Adjoua Yeboua Florence; Kamagate, Adama; Yapo, Angoué Paul (European Scientific Journal, ESJ, 2017)
Obesity is one of the diseases whose situation has become alarming in CÃ´te d’Ivoire. As it is known, the young people represent the labor force of tomorrow. So we investigated the situation of obesity among youth. We took the case of Nangui Abrogoua University which is full of students from Ivory Coast, as well as students from countries in the sub region. Our study shows that the majority of students, about 74.01 % had a normal weight. There is however 20.51% who was overweight, and 1.13% who was obese. Also overweight and abdominal obesity were more present in women than men. This low rate of obesity was explained by the fact that it is a more active population with a lower level of income. Our study highlighted that in addition to physical inactivity, obesity is also related to income level.